2019
DOI: 10.3748/wjg.v25.i32.4580
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis delta: A state-of-the-art review and new therapies

Abstract: Chronic delta hepatitis is the most severe form of viral hepatitis affecting nearly 65 million people worldwide. Individuals with this devastating illness are at higher risk for developing cirrhosis and hepatocellular carcinoma. Delta virus is a defective RNA virus that requires hepatitis B surface antigen for propagation in humans. Infection can occur in the form of a co-infection with hepatitis B, which can be self-limiting, vs superinfection in a patient with established hepatitis B i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 150 publications
(161 reference statements)
1
20
2
3
Order By: Relevance
“…The male predominance found in this work is the same as that found by Stockdale et al in 2017 [25] in London and Luma et al in Cameroon in 2017 [23]. The risk factors found in delta virus infection are mainly male homosexuality, intravenous drug use, human immunodeficiency virus (HIV), hepatitis C virus infection and sexual intercourse with multiple partners [26,27]. The VR was 67.67% in this work.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The male predominance found in this work is the same as that found by Stockdale et al in 2017 [25] in London and Luma et al in Cameroon in 2017 [23]. The risk factors found in delta virus infection are mainly male homosexuality, intravenous drug use, human immunodeficiency virus (HIV), hepatitis C virus infection and sexual intercourse with multiple partners [26,27]. The VR was 67.67% in this work.…”
Section: Discussionsupporting
confidence: 87%
“…It has been shown that in addition to the effect on virological response, it also has a significant effect on transaminase normalization, fibrosis regression and even survival [26]. The use of a combination of interferon and analogues in the treatment of HDV has not demonstrated its effect [26,27]. The persistence of Delta viral replication is a predictive factor of mortality [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of HDV infection is high in injection drug users, patients with multiple sexual partners, men who have sex with men, individuals infected with human immunodeficiency virus (HIV) or hepatitis C virus (HCV) and people from endemic areas . Soon after the discovery of HDV, injection drug users sharing needles were recognized as the major victims of this infection, with reported anti‐HDV rates in HBsAg‐positive patients in the 1980s ranging from 17% in Southern Europe to more than 90% in South Eastern Asia.…”
Section: High Risk Populationsmentioning
confidence: 99%
“…No US Food and Drug Administration-approved treatment of HDV exists, and the only somewhat effective treatment is pegylated interferon, with only 25% to 30% of patients able to control the virus with weekly injections administered for at least 1 year (17,18). When coinfection is poorly controlled, patients are 3 times as likely to develop cirrhosis and liver cancer, compared with HBV infection alone.…”
Section: Introductionmentioning
confidence: 99%